KARATERISTIK SIFAT FISIKA BAMBU TALI (GIGANTOLOCHLOA APUS KURZ ), SEBAGAI BAHAN BAKU BAMBU KERAJINAN - Febriana Tri Wulandari (Jurnal Belantara, 2020)
The centre of bamboo crafts in Gunung Sari District is the largest bamboo centre in West Lombok Regency. One of the bamboo species which is usually used as raw materials is tali bamboo. Studies of physical properties of this bamboo have not been carried out resulting poor quality of bamboo crafts. The physical property was essensial information which would be used for enhancing the products because it correlated with dimensional stability of the bamboo. The objectives of this study were to identify the physical properties of the bamboo with reference to the axial direction. The experiment design was complete random design employing the axial directions (bottom, middle, and top portions) as treatments. The statistical analyses were Anova with range tests at α = 5%. The results showed that the physical properties were: fresh moisture content 51-119.82%; air-dried moisture content 13.03-15.04%; fresh volume density 0.51 – 0.72; air-dried volume density 0.62 – 0.75; oven volume density 0.63 – 0.78. Axial directions of the physical properties were not significantly different except for the fresh moisture content. Therefore all portions of tali bamboo (bottom, middle, and top portions) could be utilized as raw materials for bamboo crafts.